2012
DOI: 10.1016/j.physbeh.2012.06.019
|View full text |Cite
|
Sign up to set email alerts
|

Early and late neurodegeneration and memory disruption after intracerebroventricular streptozotocin

Abstract: Glucose metabolism and insulin signaling disruptions in the brain have been proposed as a likely etiology of Alzheimer's disease. The aim of the present study was to investigate the time course of cognitive impairments induced by intracerebroventricular injection of streptozotocin (STZ) in rats and correlate them with the ensuing neurodegenerative process. Early and late effects of STZ were evaluated by using the reference and working memory versions of the Morris' water maze task and the evaluation of neurode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
33
0
7

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(53 citation statements)
references
References 52 publications
5
33
0
7
Order By: Relevance
“…To the best of our knowledge, this is the first in situ evidence of increased AT8 accumulation in STZ-icv rat model of sAD. Immunoblotting analysis has shown that 15 days after the STZ-icv treatment the expression of phospho (Ser199/202) tau protein is increased in rat neocortex and basal ganglia while no changes can be observed in the hippocampal region (Santos et al 2012). Clinical studies indicate that tau protein is modified at the site recognized by antibody AT8 much earlier than the appearance of aggregated (fibrillar) tau, suggesting that phosphorylation at the AT8 site represents an earlier change than tau aggregation (pretangle stage) (Braak et al 1994;Delacourte et al 1999).…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, this is the first in situ evidence of increased AT8 accumulation in STZ-icv rat model of sAD. Immunoblotting analysis has shown that 15 days after the STZ-icv treatment the expression of phospho (Ser199/202) tau protein is increased in rat neocortex and basal ganglia while no changes can be observed in the hippocampal region (Santos et al 2012). Clinical studies indicate that tau protein is modified at the site recognized by antibody AT8 much earlier than the appearance of aggregated (fibrillar) tau, suggesting that phosphorylation at the AT8 site represents an earlier change than tau aggregation (pretangle stage) (Braak et al 1994;Delacourte et al 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Selection of antibodies which target different epitopes (e.g. only Ser396 or Ser 396/404 and many other epitopes) of phospho-tau protein might also account for some inconsistency in reports of increased p-tau in cerebrum, hypothalamus and HPC (Deng et al 2009;de la Monte et al 2006;Lester-Coll et al 2006;Yang et al 2014) and unchanged p/t tau ratio in HPC (Santos et al 2012) found up to 1 month after STZ-icv treatment Although the expression of tau mRNA has been increased as early as 2 ↓ weeks after STZ-icv administration, it seems to be just a transient acute effect since it has not affected the tau protein expression and tau gene expression has not been altered in any of the time-points afterwards. The work of others indicates that tau mRNA decreases 2 and 4 weeks after the treatment (de la ) which could be due to the fact that the research was done on the rat pups and because only one house keeping gene for normalisation of gene expression was used instead of 3 house-keeping genes used in our experiments.…”
Section: Discussionmentioning
confidence: 99%
“…This decision was based on Santos et al (2012), who reported working memory disruptions three hours after icv-STZ injection, followed by degenerative processes already at day 1 post-injection. Nevertheless, all of our subjects were showing normal behavioral signs (including eating and drinking) at day 2 post-STZ, and care was taken to minimize their suffering.…”
Section: Stz Injection and Nic Treatmentmentioning
confidence: 99%